FRI0045 Expression of IL-17A, IL-17F and their receptors in inflammatory arthritis: IL-17A expression in synovium and skin is differentially regulated by adalimumab. (23rd January 2014) - van Baarsen, L.G.; Lebre, M.C.; van der Coelen, D.; Aarrass, S.; Ramwadhdoebe, T.H.; Teunissen, M.B.; van Kuijk, A.W.; Gerlag, D.M.; Tak, P.P.
Abstract : Background: Accumulating evidence suggests an important role for interleukin (IL)-17 in the pathogenesis of several inflammatory diseases, including rheumatoid arthritis (RA), psoriatic arthritis (PsA) and psoriasis. IL-17A has been well studied in models of arthritis, but little is known about the relative expression and cellular source(s) of IL-17A, IL-17F, and their receptors in human synovial tissue and psoriatic skin. Objectives: To determine the origin and expression of IL-17A, IL-17F and their receptors IL-17RA and IL-17RC in synovium and skin of patients with arthritis and their change upon anti-TNF treatment. Methods: Synovial biopsies were obtained from patients with RA (n=13), PsA (n=15) and inflammatory osteoarthritis (OA, n=14). In addition, paired synovial and skin (paired lesional and non-lesional skin) samples from adalimumab treated PsA patients (n=12) were obtained before and 4 weeks after treatment. For comparison synovium (n=7) and skin (n=14) from non-inflammatory controls were included. Frozen sections were stained for IL-17A, IL-17F, IL-17RA and IL-17RC, and evaluated by digital image analysis. To determine which cells in the synovium produce IL-17A and IL-17F, double staining with CD4, CD8, CD15, CD68, CD163, CD19, CD31, Von Willebrand Factor, PNAd, Lyve-1 and tryptase was performed and evaluated by confocal microscopy. Results: Levels of IL-17A, IL-17F, IL-17RA and IL-17RC were abundantly present in synovial tissues of all patient groups and highly variable between patients. Whereas IL-17RA was mostly present in the synovial sublining, IL-17RC was abundantly expressed in the intimal lining layer. Digital image analysis showed a significant increase of only IL-17A in arthritis patients compared to non-inflamed control tissues. The expression of IL-17A, IL-17F and IL-17RA was similar in the different patient groups, while expression of IL-17RC in the intimal lining layer was significantly increased in PsA compared to OA patients. CD4 and CD8 positive cells co-stained with IL-17A and to a lesser extent with IL-17F. IL-17A and IL-17F were not expressed by CD15 en CD19 positive cells. Mast cells occasionally were positive for IL-17A/IL-17F. Interestingly, IL-17A and IL-17F staining was also observed in some macrophages as well as in endothelial cells and lymphatics. Strikingly, PsA patients treated with anti-TNF showed a significant upregulation of synovial IL-17A. In both lesional and non-lesional psoriatic skin, IL-17A and IL-17RC were abundantly present in the epidermis. Anti-TNF treatment had no effect on IL-17A and IL-17RC expression in psoriatic skin. Conclusions: Increased expression of IL-17A is not restricted to synovial tissues of RA and PsA patients but also observed in inflammatory OA. In inflamed synovium various cell types contribute to the production of IL-17A and IL-17F. Regulation of IL-17A by anti-TNF is dependent on the local tissue environment. Disclosure of Interest: None Declared